2017
DOI: 10.1515/dcse-2017-0015
|View full text |Cite
|
Sign up to set email alerts
|

Learning from the Past for the Future: How to Make Adult Education Sustainable

Abstract: When compared to education with children, adolescents and students, adult education has particular opportunities and challenges, depending on stronger biographical influences: adults have developed their own learning style and learning competence and apart from more formal learning opportunities facilitated through digital learning and/ or learning in schools/ universities, there are many opportunities for informal learning, often influenced by experiences of education as a child. In this regard, biographical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…In concise, the present study aimed to investigate how a careless language in book reviews could negatively affect the book as well as readersí decision on buying the book. Last, by building awareness regarding the importance of a balanced language in book review, this study aimed to mark the necessity of sustainable education, which is an issue that has been rigorously researched by academics from a wide range of fields (SalÓte, 2008;Pipere, 2016;Franzenburg, 2017;Hiller & Reichhart, 2017). The importance of objective language in book reviews is recommented to be added into contents of any courses on academic writing because it should not be forgotten that ìWorking towards sustainable education will demand whole system reform (Branden, 2012, p. 299)î This study did not draw any distinction based on gender differences, and investigated reviews only on ELT not to expand the scope of the aim to be able to better focus on it.…”
Section: Resultsmentioning
confidence: 99%
“…In concise, the present study aimed to investigate how a careless language in book reviews could negatively affect the book as well as readersí decision on buying the book. Last, by building awareness regarding the importance of a balanced language in book review, this study aimed to mark the necessity of sustainable education, which is an issue that has been rigorously researched by academics from a wide range of fields (SalÓte, 2008;Pipere, 2016;Franzenburg, 2017;Hiller & Reichhart, 2017). The importance of objective language in book reviews is recommented to be added into contents of any courses on academic writing because it should not be forgotten that ìWorking towards sustainable education will demand whole system reform (Branden, 2012, p. 299)î This study did not draw any distinction based on gender differences, and investigated reviews only on ELT not to expand the scope of the aim to be able to better focus on it.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, appointments to the position of Religious Education Leader are for three years however some scholars have calculated the average appointment turnover rate to be less than eighteen months (Blahut & Bezzina, 1998;Fleming, 2004). The insights gleaned from the perspective of the participants involved in this study suggest that the following factors compromise the potential to sustain religious education leaders in seeing out the full term of their appointment: a sense of disconnection, lack of qualifications, demands of the role, and lack of support.…”
Section: Resultsmentioning
confidence: 99%
“…This perceived lack of understanding can be linked to the biases of many principals pertaining to the employment of religious education leaders. A major study about perceptions of the role of the religious education leader undertaken by Fleming (2004) revealed that in general, principalsí appointments to this positon were biased towards those who could lead religious services such as public worship and reflection days. These appointment choices were made despite the position of religious education leader being advertised as a senior leadership position requiring expertise in leading in all aspect of schools life including; curriculum, pastoral care, mission, strategic development.…”
Section: It Is As If They [Other Executive Team Members] See the Rolementioning
confidence: 99%
See 2 more Smart Citations